2020
DOI: 10.1186/s13052-020-00883-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving diagnosis for rare diseases: the experience of the Italian undiagnosed Rare diseases network

Abstract: Background For a number of persons with rare diseases (RDs) a definite diagnosis remains undiscovered with relevant physical, psychological and social consequences. Undiagnosed RDs (URDs) require other than specialised clinical centres, outstanding molecular investigations, common protocols and dedicated actions at national and international levels; thus, many “Undiagnosed RDs programs” have been gradually developed on the grounds of a well-structured multidisciplinary approach. Methods The Italian Undiagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…We next pooled genetic and clinical de-identified data of patients with severe developmental disorder (DD) enrolled in the Italian Undiagnosed Rare Diseases Network (IURDN) ( n = 110) 30 and the Deciphering Developmental Disorders study ( n = 13 462) 47 and identified 3 individuals harbouring the de novo variants c.1652G>A (p.G551E) (Fam. IV.1) and c.2219G>A (p.R740Q) (Fam.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next pooled genetic and clinical de-identified data of patients with severe developmental disorder (DD) enrolled in the Italian Undiagnosed Rare Diseases Network (IURDN) ( n = 110) 30 and the Deciphering Developmental Disorders study ( n = 13 462) 47 and identified 3 individuals harbouring the de novo variants c.1652G>A (p.G551E) (Fam. IV.1) and c.2219G>A (p.R740Q) (Fam.…”
Section: Resultsmentioning
confidence: 99%
“…II-XIV: Details on sequencing, alignment, variant calling (inherited and de novo ) and variant annotation have been described previously. 30–36 Presence or absence of the disease-causing variants was confirmed on DNA of the proband and additional members from each family by Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…We next pooled genetic and clinical de-identified data of patients with severe developmental disorder (DD) enrolled in the Italian Undiagnosed Rare Diseases Network (IURDN) (n=110) (Salvatore et al, 2020) and the Deciphering Developmental Disorders study (n = 13,462) (Barash et al, 2010) and identified 3 individuals harbouring the de novo variants c.1652G>A (p.G551E) (Fam. IV.1) and c.2219G>A (p.R740Q) (Fam.…”
Section: Resultsmentioning
confidence: 99%
“…Fam. II-XIV: Details on sequencing, alignment, variant calling (inherited and de novo) and variant annotation have been described previously (Kaplanis et al, 2020;Kinay et al, 2018;Mazzola et al, 2020;McRae et al, 2017;Muona et al, 2015;Niestroj et al, 2020;Salvatore et al, 2020). Presence or absence of the disease-causing variants was confirmed on DNA of the proband and additional members from each family by Sanger sequencing.…”
Section: Sequencing and Genotypingmentioning
confidence: 99%
“…Appropriate and timely diagnosis improves patient health status, reducing psychological and social burden of the diseases and allowing proper genetic counselling [ 49 ]. The Italian Undiagnosed Rare Diseases Network [ 50 ] collected information of 110 cases between March 2016 and June 2019. The goal of the network was to make timely and appropriate diagnoses of the most complex disorders.…”
Section: Introductionmentioning
confidence: 99%